A CRASH simulation of the contribution of binary stars to the epoch of reionization. Issue 1 (13th April 2022) - Ma, Qing-Bo; Fiaschi, Silvia; Ciardi, Benedetta; Busch, Philipp; Eide, Marius B
ABSTRACT: We use a set of three-dimensional (3D) radiative transfer simulations to study the effect that a large fraction of binary stars in galaxies during the epoch of reionization has on the physical properties of the intergalactic medium (i.e. the gas temperature and the ionization state of hydrogen and helium), on the topology of the ionized bubbles and on the 21 cm power spectra. Consistently to previous literature, we find that the inclusion of binary stars can speed up the reionization process of H i and He i, while He ii reionization is still dominated by more energetic sources, especially accreting black holes. The earlier ionization attained with binary stars allows for more time for cooling and recombination so that gas fully ionized by binary stars is typically colder than gas ionized by single stars at any given redshift. With the same volume averaged ionization fraction, the inclusion of binary stars results in fewer small ionized bubbles and more large ones, with visible effects also on the large scales of the 21 cm power spectrum.